Cytotoxic capacity of a novel glycosylated antitumor ether lipid in chemotherapy-resistant high grade serous ovarian cancer in vitro and in vivo - Mark W Nachtigal; Paris Musaphir; Shiv Dhiman; Alon D Altman; Frank Schweizer; Gilbert Arthur (Translational Oncology, 2021)
Chemotherapy resistant high grade serous ovarian cancer remains a clinically intractable disease with a high rate of mortality. We tested a novel glycosylated antitumor ether lipid called l-Rham to assess the in vitro and in vivo efficacy on high grade serous ovarian cancer cell lines and patient samples. l-Rham effectively kills high grade serous ovarian cancer cells grown as 2D or 3D cultures in a dose and time dependent manner. l-Rham efficacy was tested in vivo in a chicken allantoic membrane/COV362 xenograft model, where l-Rham activity was as effective as paclitaxel in reducing tumor weight and metastasis. The efficacy of l-Rham to reduce OVCAR3 tumor xenografts in NRG mice was assessed in low and high tumor burden models. l-Rham effectively reduced tumor formation in the low tumor burden group, and blocked ascites formation in low and high tumor burden animals. l-Rham demonstrates efficacy against OVCAR3 tumor and ascites formation in vivo in NRG mice, laying the foundation for further development of this drug class for the treatment of high grade serous ovarian cancer patients.